DNA methylation testing with S5 for triage of high‐risk HPV positive women. Issue 7 (24th May 2022) - Adcock, Rachael; Nedjai, Belinda; Lorincz, Attila T.; Scibior‐Bentkowska, Dorota; Banwait, Rawinder; Torrez‐Martinez, Norah; Robertson, Michael; Cuzick, Jack; Wheeler, Cosette M.; ,
Abstract: Methylation of host and viral genes is promising for triage of women with high‐risk human papillomavirus infections (hrHPV). Using a population‐based sample of hrHPV positive women with cervical biopsies within 12 months after cervical screening, the clinical value of the S5 methylation classifier (S5), HPV genotyping and cytology were compared as potential triage tests, for outcomes of cervical intraepithelial neoplasia (CIN) grade 3 or greater (CIN3+), CIN2+ and CIN2, and the area under the curve (AUC) calculated. S5 scores increased with histopathology severity ( P trend < .001). For CIN3+, the AUC was 0.780 suggesting S5 provides good discrimination between <CIN3 and CIN3+. AUCs were significant for all pairwise comparisons of <CIN2, CIN2 and CIN3+ ( P < .001). The positive predictive value (PPV) of HPV16/18 genotyping for women with any abnormal cytology was greater than S5 (25.36% vs 20.87%, P = .005) for CIN3+, while sensitivity was substantially greater for S5 (83.33% vs 59.28%, P < .001). Restricting to women with abnormal cytology, but excluding those with high‐grade cytology, both S5 and HPV16/18 provided CIN3+ PPVs high enough to recommend colposcopy. Triage with S5 also appeared useful for hrHPV positive women negative for HPV16/18 (CIN3+ PPV: 7.33%, sensitivity: 57.52%). S5 provided increased sensitivity for CIN3+ compared to HPV16/18 genotyping for hrHPV positive women, overall and when restricted to women with abnormal cytology, suggesting S5 may improve colposcopy referral. S5 also has the ability to distinguish between <CIN2, CIN2 and CIN3+, a finding of importance for managing CIN2, given the complexity and uncertainty associated with this diagnosis. Abstract : What's new? Human papillomavirus (HPV) testing is a more sensitive but less specific approach for cervical cancer screening than cytology. Methylation testing of host and viral genes has emerged as a promising approach for the triage of women with high‐risk HPV. In this population‐based study, using the DNA methylation S5 classifier as a triage test for high‐risk HPV‐positive women yields significantly greater sensitivity and similar positive predictive values for CIN3+ detection than HPV genotyping or cytology triage. Furthermore, S5 can improve discrimination between low‐ and high‐grade cervical precancer, providing valuable information in the often complex and uncertain diagnosis of CIN2.